(untitled) (Medical Forum Monthly, 2021)
Objective: This study aims to identify the risk factors and clinical prognostic scores that have a significant predictive value in RRT-dependent AKI patients who developed the disease following cardiac surgery. Study Design: A cross-sectional, analytical study Place and Duration of Study: This study was conducted at the Intensive Care Unit in Bakhtawar Amin Trust Teaching Hospital Multan from 1ST September 2020 to 1ST February 2021. Materials and Methods: A cross-sectional analysis of 35 cardiac surgery patients older than 18 years receiving RRT for treatment of cardiac surgery-related AKI. The Severity scores were recorded and potential risk factors associated with mortality in AKI were evaluated at the start of RRT. Our study defined these severity scores; "Acute Physiology and Chronic Health Evaluation (APACHE) II" as a general score, "Sequential Organ Failure Assessment (SOFA)" as an organ failure score, and "Liano score” as a renal disease severity score. Multivariable logistic regression analysis was also performed to assess the mortality-associated risk factors. Results: 5 patients (14.2%) died during the hospitalization time. 28.5% continued dialysis even after hospital discharge. The area under curve score was 0.669 for Liano, 0.722 for SOFA and 0.672 for APACHE II. The logistic regression model showed 4 variables associated with patient mortality out of the 16 selected for model selection, “Glasgow coma score < 14 points (OR=3.206,95% Cl;1.020-9.776, P=0.0027) , MAP < 63.5 mmHg (OR = 3.763, 95% CI; 1.11-13.715, P = 0.032), preoperative serum creatinine >108.5 µmol/L (OR = 0.355, 95% CI; 0.234-0.873, P = 0.040), and postoperative platelet count < 115 × 109/L (OR = 3.829, 95% CI; 1.362-11.056, P = 0.020)” significantly affected the mortality of the patients. Conclusion: Our study observed no relationship between mortality and other factors (demographic, surgical, preoperative, and postoperative variables). The SOFA score is the most reliable to predict the poor outcome at the start of RRT in both groups after 1 month following the cardiac surgery. Glasgow coma score less than 14 points, MAP less than 63.5 mmHg, preoperative serum creatinine greater than 108.5 mmol/L, and postoperative platelet count less than 115 × 109/L affected the mortality rate and were independent risk factors for lethal patient outcome.